A Lean Warehousing Approach for Waste Reduction: A Case-Based Analysis Using VSM and VALSAT - Kartika Nur 'Anisa'; Desak Made Adya Pramesti (Journal of Advanced Technology and Multidiscipline, 2025)
This study aims to identify and reduce waste in the loading and unloading processes at PT XYZ’s motorcycle distribution warehouse to improve operational efficiency. A Lean Warehousing approach was adopted, beginning with Value Stream Mapping (VSM) to visualize the current workflow and identify non-value-added activities. Waste types were quantified using the Waste Assessment Model (WAM), and improvement priorities were determined through the VALSAT tool. Further analysis with Process Activity Mapping provided a detailed evaluation of each process step, facilitating the elimination of inefficiencies. The assessment revealed that the most dominant wastes were motion (22.43%), waiting (17.70%), and processing waste (12.87%). To address these issues, root cause analysis was conducted using the Why-Why method, followed by the development of corrective actions based on 5W1H framework. Improvement strategies included workflow optimization and the implementation of standardized operational procedures. Unloading time was reduced by 22.12% (from 104 to 81 minutes), and loading time decreased by 37.65% (from 85 to 53 minutes). Moreover, Process Cycle Efficiency (PCE) significantly improved, i.e. 28.40% for unloading and 17.81% for loading. The study confirms that the structured application of lean tools can effectively eliminate non-value-added activities, improve process flow, and enhance overall warehouse performance. These findings provide practical insights for warehouse and logistics managers in implementing lean-based improvements to achieve higher operational efficiency.